Legal Review of the Basis for Judge's Considerations in Issuing a Decision to Acquit All Legal Charges for the Criminal Act of Using Land Without Permission (Study of Decision Number 7/Pid.C/Daf.Pid/2023/PN.Sbw) - Suryandari, Marnita Eka; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
Land as a gift from God Almighty is a natural resource that is greatly needed by humans to meet their needs. Land has an important role in people's lives, both as a place to live, a place to plant crops, a means of production, construction of facilities and infrastructure, and economic assets. Soil consists of mineral particles, organic matter, water, air, and living things. Given the importance of land, the management, utilization and control of land is carried out by the state. This is as mandated in Article 33 paragraph (3) of the 1945 Constitution which emphasizes that the earth, water and natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. Thus, the prosperity of the people is the spirit and ultimate goal of the welfare state which must be realized by the state and government of Indonesia. The approach method used in this research is normative juridical, namely legal research conducted by examining library materials (secondary data) which includes research on legal principles, legal systematics, the level of synchronization of laws and regulations, comparative law or legal history. Considering, that based on the facts revealed in relation to the understanding of the element of using land according to the Judge, it has been proven that the Defendants have cultivated and planted coconut trees, banana trees, corn trees and built a hut on the land, where the Defendants planted trees on the land because the Defendants believe that the land belongs to their parents named M. Daud, which statement of the Defendants is also strengthened by the statement of witnesses M. Yunus and witness Rabusi Andang, even the land has also been controlled by other parties, which is proven by the statement of witness Mardi who has purchased land from the reporting witness Fahrizal with an area of 10,000 M² (ten thousand square meters), where the land purchased by witness Mardi is a unit of land owned by M. Daud's parents with a total area of 3 (three) hectares 20 (twenty) ares where currently the Defendants control the land with an area of 22,000 M².